Neutrophil extracellular traps as markers of thromboinflammation in the pathogenesis of female genital tract and breast malignant neoplasms - E. V. Slukhanchuk; V. O. Bitsadze; A. G. Solopova; J. Kh. Khizroeva; J.-Ch. Gris; I. Elalamy; A. D. Makatsariya (Акушерство, гинекология и репродукция)
Introduction. Thrombosis is a formidable complication of the oncological process that still profoundly contributes to overall mortality despite the anticoagulant use. According to the recent data, thrombosis in cancer represents a special type of prothrombotic state, wherein thromboinflammationis one of its constituents. In addition, thromboinflammation contributes both to the disease progression and intensity of metastasis processes. Recently, a large number of studies worldwide have been devoted to investigating thromboinflammation in cancer patients.Aim: to assess NETosis activity (the process of neutrophils extracellular traps synthesis), namely, the concentration of citrullinated histone H3 (citH3) as a blood plasma NETosis marker in women with malignant genital organs and breast neoplasms.Materials and Мethods. The prospective observational controlled non-randomized study included 45 patients (main group) with malignant neoplasms of uterus body, ovaries, cervix (adenocarcinoma of the cervical canal) and mammary glands admitted to the hospital for planned surgical treatment (13, 15, 5 and 13 patients, respectively) and 33 women with benign neoplasms of the genital organs and mammary gland (control group). The plasma citН3 concentration was determined using an enzyme immunoassay.Results. It was found that cancer patients had citН3 concentration significantly increased (1.434–2.058 ng/ml) compared with the control group (0.281–0.371 ng/ml). The concentration of citH3 in patients with tumors of the uterine body and cervix ranged from 2.271 to 2.992 ng/ml, patients with ovarian tumors – from 1.357 to 2.123 ng/ml, patients with breast tumors – from 0.331 to 0.859 ng/ml. The study revealed no significant differences in the citH3 concentration in patients with breast tumors compared to the control group. Upon elevating citН3 concentration, such parameters as C-reactive protein, D-dimer, neutrophils and platelets count, as well as neutrophils/lymphocytes ratio were significantly increased. Significant differences were revealed in platelet count in the main group (236,68–273,77×109/L) vs. control group (178,14–202,35×109/L).Conclusion. The study demonstrated the activation of NETosis in patients with tumors of the uterine body as well as cervix (adenocarcinoma) and ovaries that might be combined with hemostasis activation and systemic inflammatory response.